Analisis Financial Distress Dengan Metode Springate, Grover, dan Zmijewski Pada PT Wijaya Karya (Persero) TBK Tahun 2018-2022 - Nor Latifah; Taufik Akbar; Trisnia Widuri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to investigate the financial status by conducting bankruptcy analyses using the Springate, Grover, and Zmijewski Methods on WIKA from 2018 to 2022, and to investigate the differences in the outcomes produced by these three methodologies. The method used in this study is a quantitative descriptive method. This study involved interpreting processed data through mathematical procedures, utilizing WIKA’s published financial statements from 2018 to 2022. The results show that according to the Springate method, WIKA experienced financial distress during this period. However, based on the Grover method, WIKA did not experience financial distress from 2018 to 2022. Nevertheless, according to the Zmijewski method, WIKA did not experience financial distress from 2018 to 2021 but faced a distressed situation in 2022.